Strengthening resilience in Philippine health emergency and disaster risk management: a whole-of-society approach - Downey, Erin L; Law, Ronald; Mhyco Esguerra, Princess; Capistrano, Rowena; Sekitani, Yui (Western Pacific Surveillance and Response, 2025)
This article examines the Philippines' use of a whole-of-society approach to health emergency and disaster risk management. It highlights the role of multisectoral partnerships in addressing biological and climate-related crises, offering valuable insights for improving disaster resilience across the Western Pacific Region.
Keywords: government; societies; emergencies; disasters; outbreaks; COVID-19; climate